Childhood and child labour in the British industrial revolution. - Humphries, J (Blackwell Publishing, 2012)
Quantitative and qualitative analysis of a large number of autobiographies by working men who lived through the industrial revolution has demonstrated that there was an upsurge in child labour in the late eighteenth and early nineteenth centuries with children's work entrenched in traditional sectors as well as spreading in newly mechanized factories and workshops. I have interpreted this rise in terms of the appearance of a new equilibrium in the early industrial economy with more and younger children at work. The new equilibrium, in turn, was related to a number of co-incidental developments including: an increase in the relative productivity of children as a result of mechanization, new divisions of labour, and changes in the organization of work; the dynamics of competitive dependence linking labour market and families; high dependency ratios within families; stumbling male wages and pockets of poverty; family instability; and breadwinner frailty. The establishment of these links forges a new synchronization between revised views of the industrial revolution and a revisionist history of child labour.